2007
DOI: 10.1210/en.2006-1473
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Couples to 3′,5′-Cyclic Adenosine-5′-Monophosphate Pathway through Novel Protein Kinase Cδ and -ε in LβT2 Gonadotrope Cells

Abstract: GnRH regulates the reproductive system by stimulating synthesis and release of gonadotropins. GnRH acts through a receptor coupled to multiple intracellular events including a rapid phosphoinositide turnover. Although the cAMP pathway is essential for gonadotrope function, the ability of GnRH to induce cAMP, as well as the coupling mechanisms involved, remain controversial. In this study, we established that GnRH increases intracellular cAMP levels in a concentration-dependent manner in LbetaT2 gonadotrope cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 49 publications
2
46
1
Order By: Relevance
“…It has been reported that PKC␦ and PKC⑀ are the two endogenous isoforms mediating GnRH action on the activation of AC/cAMP pathway in L␤T2 cells (36). To date, AC2, AC5, and AC7 have been shown to be directly phosphorylated by PKC (54 -56), and two PKC-sensitive AC isoforms, AC5 and AC7, seem to be the potential targets for GnRH stimulation in L␤T2 cells (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PKC␦ and PKC⑀ are the two endogenous isoforms mediating GnRH action on the activation of AC/cAMP pathway in L␤T2 cells (36). To date, AC2, AC5, and AC7 have been shown to be directly phosphorylated by PKC (54 -56), and two PKC-sensitive AC isoforms, AC5 and AC7, seem to be the potential targets for GnRH stimulation in L␤T2 cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…To date, AC2, AC5, and AC7 have been shown to be directly phosphorylated by PKC (54 -56), and two PKC-sensitive AC isoforms, AC5 and AC7, seem to be the potential targets for GnRH stimulation in L␤T2 cells (36). These reports indicate that the AC/cAMP/PKA pathway is also activated via G␣ q/11 -mediated PKC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The former messenger diffuses through the cytoplasm, promoting the release of intracellular calcium and the release of both gonadotropins. More recently, coupling of the GnRHR to the cAMP pathway has been shown under conditions of sustained stimulation, which may be potentially important under intense GnRH release, such as the preovulatory GnRH surge (Larivière et al, 2007).…”
mentioning
confidence: 99%
“…In LβT2 gonadotrope cells, GnRHR receptor stimulation was found to increase intracellular cAMP in a dose dependent fashion, and to increase a cAMP responsive reporter gene [23]. Also, in GH-secreting adenomas, GnRHR increased intracellular calcium levels, cAMP, and AC activity measured in membrane preparations [24].…”
Section: Discussionmentioning
confidence: 85%